New industrial policy for more inclusive and sustainable growth - David Bailey; Lisa De Propris; Jürgen Janger (WWWforEurope, 2015)
The policy brief synthesises key policy findings from Area 3. The over-riding goal is to foster the transition to a new growth path for Europe, with a dynamic manufacturing and services base, greater social inclusiveness, less unemployment and higher sustainability based on excellence in clean technologies. Embarking on a growth path that leverages current technological chances, that is ecologically compatible and that delivers greater and more shared prosperity requires a vision that is able to set long term, clear and transparent targets and to draw pathways to reach them. Businesses require certainty to take risks and create the jobs that societies and communities need to flourish and prosper. Economic growth, social inclusion and ecological ambitions are not necessarily mutually exclusive, but neither are they mutually supportive. In the New Industrial Policy that this brief presents, we see a real opportunity for developing a policy agenda that is capable of transforming some of the trade-offs into potential synergies, problems into solutions and constraints into advantages. Our research has encompassed five key questions: (a) How can we redefine competitiveness so as to encompass social and ecological objectives and to motivate a new industrial policy needed for technology shifts and inclusive, sustainable growth? (b) How do we realign innovation and industrial performance towards social and ecological objectives? (c) What is the impact of green innovation on growth, employment and social cohesion? (d) How can entrepreneurial dynamics drive smart and sustainable growth? (e) How can intangible assets and the quality of academic research act as drivers of change? This Policy Brief outlines the essential elements of the New Industrial Policy for Europe (NIPE) for a more smart, inclusive and sustainable growth.
Keywords: O25; L52; 330; Economic growth path; economic strategy; holistic and interdisciplinary approach; industrial policy; policy options; political economy of policy reform; social development; sustainable growth